The The Role of Social Media as a Support Medium for Independent Training for Student Athletes Post-COVID-19 - Marvel Panjita Raja Oloan Pardede; Surdiniaty Ugelta; Septian Williyanto; Mustika Fitri; Mohammad Zaky (Universitas Negeri Jakarta Postgraduate of Physical Education Departments, 2025)
The post-pandemic era has transformed athletes’ training habits, with social media emerging as a vital medium that supports independent training among student athletes. Despite its growing use, limited studies have examined its post-pandemic impact. This study aims to explore how social media contributes to athletes’ motivation, consistency, and independence in training when traditional facilities have resumed. Method: Using a qualitative design, eight student athletes were purposively selected. Data were collected through in-depth interviews and analyzed using the Miles and Huberman interactive model to identify key themes. Findings reveal that social media platforms such as Instagram, TikTok, and YouTube serve as alternative learning spaces for technical, physical, and mental training. They enhance flexibility, motivation, and engagement. Social media significantly supports self-directed learning and motivation, complementing conventional training methods while fostering independence, discipline, and innovation among student athletes in the post-COVID-19 context .